Empirical Evaluation of Educational Service Quality in the Current Higher Education System - Lili Abdullah Rozak; M. Bahri Arifin; Inna N. Rykova; Olga A. Grishina; Aan Komariah; Diding Nurdin; Vadim V. Ponkratov; Gevorg T. Malashenko; Mikhail E. Kosov; Olesya V. Dudnik (Emerging Science Journal, 2022)
During the transition to the mixed education model during the Covid-19 pandemic, some issues have emerged in the matter of providing and supporting the quality of university education in all countries, including educational programs' relevance to the demands of the labor market, expectations of students and their families, digital transformation of the educational process, and economic stability of institution networks. The purpose of the research was to evaluate the quality of educational services in the higher education systems of Indonesia and Russia. The study systematized several essential factors for achieving educational service quality in the current higher education systems, given the limitations imposed by Covid-19. Following this objective, the study utilized a quantitative approach, adopting the SERVQUALmodel that measures the service quality across five service dimensions: tangibility, reliability, responsiveness, assurance, and empathy. The model aided the development of the questionnaire to assess the quality of the educational services of Indonesian and Russian universities. The questionnaire included 25 close-ended questions on two scales: one to measure the students' expectations regarding the quality of educational services and the other to measure the students' current perceptions. A snowball technique was used to recruit students from Indonesian and Russian universities as participants in the study. The students were asked to assess the educational services of their universities based on their initial expectations and current perceptions. Overall, the students of both countries revealed that they had high expectations from the educational services of their universities. However, the current perceptions of the Russian students regarding the quality of educational services provided by their universities are higher and more positive than the perceptions of the Indonesian students regarding the quality of educational services being delivered to them. The findings of the study have implications for education practitioners. Doi: 10.28991/ESJ-2022-SIED-05 Full Text: PDF